1981
DOI: 10.1111/j.1365-2133.1981.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the plasma membrane of normal and psoriatic keratinocytes. 4. Characterization of glycoconjugates

Abstract: A substantial proportion (20-50%) of radioactive sugar incorporated into glycoconjugates by normal human keratinocytes was soluble in chloroform-methanol; using (14C)-galactose as precursor about half of this fraction was neutral lipid. The incorporation of labelled sugars into the lipid fraction was consistently increased in keratinocytes derived from psoriatic lesions. The abnormality in fucose metabolism which we reported previously has been confirmed. In particular we have shown that the molecular weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Thus we must assume either structural changes in the oligosaccharide moieties in particular glycoproteins or an alteration in the relative amounts ofthe different types of glycoprotein. The marked increase in the association constant of UEA (fucose-binding) is noteworthy, and may be correlated with the changes in molecular weight distribution of total membrane glycopeptides found after labelling with fucose (Roelfzema et al, 1981b).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Thus we must assume either structural changes in the oligosaccharide moieties in particular glycoproteins or an alteration in the relative amounts ofthe different types of glycoprotein. The marked increase in the association constant of UEA (fucose-binding) is noteworthy, and may be correlated with the changes in molecular weight distribution of total membrane glycopeptides found after labelling with fucose (Roelfzema et al, 1981b).…”
Section: Resultsmentioning
confidence: 70%
“…A marked increase in the affinity of the cell surface for Ulex europus agglutinin (fucose-specific) confirms our previous reports of structural alterations in fucose-containing oligosaccharides in psoriasis.In previous papers in this series we have reported profound abnormalities in the metabolism of certain sugars by psoriatic keratinocytes. Disturbances include an increased rate of entry of labelled sugars into the cell and of their incorporation into glycoconjugates (Roelfzema et al, 1981 a) and changes in the structure of the oligosaccharide fragments remaining after proteolytic digestion of cellular glycoprotein (Roelfzema et al, 1981b). Such findings are compatible with the altered cell cycle kinetics of the psoriatic lesion, since the surface receptors which couple the external milieu to the intracellular regulators are mostly glycoprotein in nature (Kahn, 1976).A direct analysis of the carbohydrate content of glycoconjugates located on the cell surface would therefore be very useful in extending these findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Roelfzema et al [19] have shown the incor poration of labelled sugars into glycoproteins, glycolipids and proteoglycans by keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These lipid bilayers include very little of phospholipids thought to be essential for the arrange ments of lipids into bilayers. However, it is thought that sphingolipids and sterols help in the maintenance of bilayer structure [9,10,19] and that these lipids and glycoconjugates may be the macromolecules which mask the SCAg.…”
Section: Discussionmentioning
confidence: 99%